Correlation analysis between the severity of respiratory syncytial virus pneumonia and the expression levels of inflammatory cytokines in bronchoalveolar lavage fluid among infants and young children - Tan, Lin; He, Zhaohui; Liang, Yongqi; Wang, Kuncheng; Chen, Xiaoqian (Frontiers in Pediatrics, 2025)
PurposeRSV is the primary cause of lower respiratory tract infections in infants and young children. Current study aims to investigate the correlation between the severity of respiratory syncytial virus pneumonia (RSVP) in infants and young children and the number of RSV infection sequences as well as the levels of cytokines in bronchoalveolar lavage fluid (BALF).MethodsMetagenomics next-generation sequencing (mNGS) and enzyme-linked immunosorbent assay (ELISA) were used to detect the number of RSV infection sequences and the levels of related inflammatory cytokines in BALF samples. Comparisons between groups and Logistic regression analysis were performed to examine the differences in RSV infection sequences and inflammatory cytokine levels between the sRSVP and nsRSVP groups. Spearman's correlation coefficient was used to analyze the correlations among PCIS, RSV infection sequences, and inflammatory cytokines. Finally, ROC curve analysis was conducted to assess the diagnostic performance of inflammatory cytokines as biomarkers in determining the severity of RSVP.ResultsA total of 49 infants and young children diagnosed with RSV infection were enrolled and divided into severe RSVP (sRSVP) and non-severe RSVP (nsRSVP) groups based on the pediatric critical illness score (PCIS) scale. The levels of Interleukin (IL)-6, IL-8, IL-10, tumor necrosis factor α (TNF-α), IL-17A, and monocyte chemotactic protein 1 (MCP-1) as well as the number of RSV sequences in BALF were significantly higher in the sRSVP group than in the nsRSVP group. Additionally, elevated levels of IL-6, IL-10, TNF-α, IL-17A, and the number of RSV sequences were identified as risk factors for the severity of RSVP. Spearman's correlation analysis revealed significant negative correlations between the levels of IL-6, IL-10, TNF-α, IL-17A, and MCP-1 in BALF with PCIS, and significant positive correlations with the number of RSV sequences. Furthermore, a significant negative correlation was observed between RSV sequence count and PCIS. ROC curve analysis showed that the levels of IL-6, IL-10, TNF-α, IL-17A, and MCP-1, as well as their combined diagnostic approach, exhibited high diagnostic performance in determining the severity of RSVP.ConclusionThe levels of inflammatory cytokines and RSV sequences in BALF are significantly correlated with the severity of RSVP in infants and young children. The levels of IL-6, IL-10, TNF-α, IL-17A, and MCP-1 can serve as potential biomarkers for diagnosing the severity of RSVP.